ʿAyn al-Quḍāt between Divine Jealousy and Political Intrigue - Rustom, Mohammed (Journal of Sufi studies, 2018)
Modern scholars have been interested in the great Persian Sufi martyr ʿAyn al-Quḍāt Hamadānī (d. 525/1131) for over six decades. Despite this fact, many aspects of his life and thought still remain terra incognita. Our knowledge of the circumstances surrounding his death is a case-in-point. Although we have a fairly good understanding of the factors which led to ʿAyn al-Quḍāt's demise, there are other "causes" which simultaneously complement and problematize this understanding. Chief amongst these are the underlying reasons for ʿAyn al-Quḍāt's critique of the Seljuk government, as well as something which ʿAyn al-Quḍāt saw as a more subtle cause for his death several years before his anticipated state execution.